2011
DOI: 10.1002/art.30415
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatocyte growth factor promoter polymorphism with severity of interstitial lung disease in Japanese patients with systemic sclerosis

Abstract: Objective. To examine associations of singlenucleotide polymorphisms (SNPs) within genes for hepatocyte growth factor (HGF) and its receptor c-met with disease susceptibility and organ involvement in Japanese patients with systemic sclerosis (SSc).Methods. Four SNPs (HGF -1652 C/T, ؉44222 C/T, and ؉63555 G/T, and c-met -980 T/A) were analyzed in 159 SSc patients and 103 healthy control subjects with the use of a polymerase chain reactionbased assay. The influence of the HGF -1652 SNP on transcription activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…One SNP in HGF , rs3735520 (c.−1652C > T), was reported to modulate the severity of interstitial lung disease in patients with systemic sclerosis by altering the transcriptional efficiency of the HGF gene 67 . Whether they are in linkage disequilibrium with other coding variants in the relevant genes remained to be elucidated by sequencing analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One SNP in HGF , rs3735520 (c.−1652C > T), was reported to modulate the severity of interstitial lung disease in patients with systemic sclerosis by altering the transcriptional efficiency of the HGF gene 67 . Whether they are in linkage disequilibrium with other coding variants in the relevant genes remained to be elucidated by sequencing analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In 78 control participants from the Cardiovascular Health Study, SNP rs3735520, which is located in the promoter region of the HGF gene, was statistically significantly associated with HFG levels, whereas SNP rs17501108 (likewise located in the promoter) was not. 21 However, SNP rs3735520 was not associated with HGF levels in 133 patients with systemic sclerosis, 22 although experimental data indicated that this variant was related to transcriptional activity. 22 In our dataset, both SNP rs3735520 (p=0.12) and SNP rs17501108 (p=0.39) were not associated with HGF concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, SNP rs3735520 was not associated with HGF levels in 133 patients with systemic sclerosis, 22 although experimental data indicated that this variant was related to transcriptional activity. 22 In our dataset, both SNP rs3735520 (p=0.12) and SNP rs17501108 (p=0.39) were not associated with HGF concentrations. Thus far, there has been no genome-wide analysis regarding the genetic determinants of HGF levels.…”
Section: Discussionmentioning
confidence: 99%
“…SNP Rs3735520 was found to associate with end-stage lung disease in Japanese systemic sclerosis patients, and carriers of the HGF promoter with the HGF − 1652 TT allele had a relative inability to increase circulating HGF levels. By functional studies, the HGF promoter carrying the HGF − 1652 TT allele was reported to have lower transcriptional activity than the promoter carrying the CT or CC allele, possibly due to the binding of a negative transcriptional regulator [37]. In myeloma, the relevance of these SNPs, in particular Rs3735520, needs further clarification.…”
Section: Discussionmentioning
confidence: 99%